La reputación del sujeto obligado en procesos comerciales o contractuales con personas políticamente expuestas - Bonilla Muñoz, Leslie Jael (2025)
Reputation management is a critical aspect of obligating entities in commercial or contractual processes with politically exposed persons (PEPs) due to the high risk associated with these relationships. This study explores how companies, including financial institutions, law firms, and other regulated entities, perceive and manage reputational risks arising from their links with PEPs. Qualitative analysis was used since there was a theoretical development that allowed for the investigation of new perspectives and the construction of emerging theories on the relationship between reputation and interactions with PEPs. The main risk perceptions impact reputation, and mitigation strategies adopted by obligated entities are identified. The results reveal that relationships with PEPs are seen as high-risk due to the potential for corruption, bribery, and money laundering, factors that can cause significant damage to corporate reputation. Exposure to reputational risks not only implies a lack of confidence from stakeholders but also increased compliance and operational costs, as well as a reduction in market capitalization.